PRESENT SITUATION ANALYSIS FOR ESP COURSE OF MECHANICAL ENGINEERING STUDENTS OF TRIDINANTI UNIVERSITY - Sari, Farnia; Setiawan, Heru; Tridinanti, Gaya (Universitas Muhammadiyah Palembang, 2020)
This paper presents and examines the students’ present situation analysis of mechanical engineering. In order to investigate present situation analysis, the data is collected through questionnaires of present situation analysis are distributed to the students of mechanical engineering study program with the total 111 students. A qualitiative with descriptive research method is adopted for this evaluation study. The results generated by PSA questionnaire is shown that the students learning input including listening input, speaking input, reading input, and writing input. Based on the findings, most of the students’ proficiency levels at beginner category. Regarding listening input, the students’ preferences input for listening used authentic materials and the topic preferences of students were about daily routines. Speaking input, most of the students’ input for speaking preferred monologue and dialogue with new vocabularies list and phonetic transcription with the desired topic for speaking input that was mechanical engineering field. Reading input, students’ preferences for reading input were authentic materials closely related to daily life with the topics desired for reading input was daily routines. Writing input, the students preferred to the explaination of the structures of the text related to the topics with the length of words was 100 – 150 words.